Freestanding Needle Flower Structure CuCo2S4 on Carbon Cloth for Flexible High Energy Supercapacitors With the Gel Electrolyte - Xie, Tian; Xu, Jinxiao; Wang, Jie; Ma, Chuanli; Su, Linghao; Dong, Fengying; Gong, Liangyu (Frontiers in Chemistry, 2020)
A facile approach of hydrothermal was proposed to fabricate direct synthesis of the bimetallic sulfide (CuCo2S4) on carbon cloth (CC) without binders for supercapacitors electrodes, and proposed a possible formation mechanism. The prepared CuCo2S4/CC exhibits high SC of 1312 F· g -1 at 1 A· g -1and an excellent capacitance retention of 94% at 5 A· g -1 over 5000 cycles. In addition, the asymmetric supercapacitor (CuCo2S4/CC//AC/CC) exhibits energy density (42.9 wh· kg -1 at 0.8 kW· kg -1 ) and outstanding cycle performance (80% initial capacity retention after 5000 cycles at 10 A· g -1 ). Meanwhile, the electrochemical performance of supercapacitor device is still quite stable at different angles of bending. Two charged device in series can light 28 red color LED's (2 V) for 5 minutes. This all indicates that the prepared CuCo2S4 has potential application value.